Structure and property changes of polyamide 6 during the gel‐spinning process. Issue 6 (24th July 2013) - Zhang, Huimin; Shi, Chaoming; He, Miaomiao; Jia, Qingxiu; Zhang, Liqun
ABSTRACT Polyamide 6 (PA6) gels were prepared by the dissolution of PA6 powder in formic acid with CaCl2 as a complexing agent. The concentration of the polymer was 16% w/v. PA6 fibers were obtained through gel‐spinning, drawing, decomplexation, and heat‐setting processes. The structure and properties of the fibers at different stages were characterized with differential scanning calorimetry, thermogravimetric analysis, X‐ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy. The experiment results indicate that the melting transition of the as‐spun fibers obtained by the extrusion of the PA6/CaCl2/HCOOH solution into a coagulation bath through a die disappeared. A porous structure existed in the as‐spun fibers, which led to poor mechanical properties. Compared with the as‐spun fibers, the melting and glass‐transition temperatures of the decomplexed and drawn fibers retained their original values from PA6, the degree of crystallinity increased, the porous structure disappeared, and the mechanical properties were improved. The maximum modulus and tensile strength obtained from the drawn fibers in this study were 32.3 GPa and 530.5 MPa, respectively, at the maximum draw ratio of 10. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 4449–4456, 2013